Non-Endoscopic Endo-nasal Dacryocystorhinostomy in a Saddle shaped nose: A Case Report - Bhattarai, Binita; Shrestha, Koshal; Manandhar, Laxmi Devi (Nepalese Journal of Ophthalmology, 2021)
Introduction: Non Endoscopic endo-nasal dacryocystorhinostomy retains the benefit of an Endo-nasal approach and can be done without using an expensive video endoscope or laser system. Case presentation: A 22 years old female presented with epiphora and medial canthal mass in her left eye, accompanied by discharge and recurrent conjunctival congestion since childhood. Physical examination revealed loss of height of the nose with discharge in her left eye, and am immobile and non-tender mass below the level of medial canthal tendon. On applying pressure over the lesion there was mucopurulent discharge from both the upper and lower punctum . The bridge of the nose was very flat and external dacryocystectomy was a challenge. A non-endoscopic endonasal dacryocystorhinostomy with silicon tube intubation was planned. During the procedure, the bone was lower than normal requiring more bone nibbling. Epiphora was resolved immediately after surgery. Conclusion: Non-Endoscopic endo-nasal dacryocystorhinostomy has the benefit of doing it through an endo-nasal approach without expensive and space consuming video-endoscope making more room for bone nibbling even in a narrow and deformed nasal cavity.